Breaking Joy Division’s “Glass”: Reading Song Lyrics as Literature - Valdés Miyares, J. Rubén (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2016)
There are various difficulties in reading the words of songs as literary texts. Principal among them is the relation of those words to the story (or star-text) of their author. The life of Ian Curtis as written by his biographers and the songs he wrote for his band, Joy Division, exemplified as they are by the symbolism of breaking glass, are a case in point. Ultimately, more than with any other literary text, their meaning depends on their refraction, analogous to that of the shards of a broken mirror, through multiple other texts and audiences. Keywords: Joy Division; song lyrics; pop/rock culture; text analysis; intertextuality; reading